CULTURAL EXPERIENCE AS MEDIATOR IN CONNECTION CUSTOMER EXPERIENCE AND CUSTOMER SATISFACTION TO CUSTOMER LOYALTY: STUDIES CASE BRAND THE SPONGE HERBS MAKASSAR - Mustikawati; Eric Harianto; Natalia Christiani (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
The competitive business environment in Makassar, particularly in the local food retail and regional souvenir sectors, is the source of this study. The Bolu Rampah, which saw a sharp drop in both visitors and revenue in 2025, has been directly harmed by this situation. The Bolu Rampah, a traditional Makassar sponge cake known for its soft texture, cinnamon aroma, and unique sweetness of palm sugar, is the signature product of the Bolu Rampah, a native Makassar brand with rich cultural roots. The Bolu Rampah has responded to this issue by implementing innovations that are intended to improve customer pleasure and experience, ultimately cultivating loyalty among its dedicated clientele. In order to create a distinct point of differentiation, the company has included local cultural features into its customer service, such as using area greetings and having customer service employees wear traditional clothing (particularly, bodo clothes). This study aims to determine the influence of customer experience and customer satisfaction on customer loyalty , mediated by cultural experience , among customers of The Sponge Herbs Makassar. The population for this studycomprises all membership customers of The Sponge Herbs in the Makassar region, who have made purchases either directly atoutlets (offline stores) or through on line platforms (on line stores) at least twice in the last six months. A sample of 312 respondentswas collected using a purposive sampling techniques. The data was analyzed using SEM-PLS using the Smart-PLS 2026 program.The outcomes of the study show that cultural experience , customer satisfaction , and customer experience all significantly impact consumer loyalty . Similarly, the cultural experience variable effectively mediates the connection between customer loyalty, customer satisfaction, and customer experience among The Sponge Herbs Makassar customers.